Time reference in Zulu - Posthumus, L. C. (South African Journal of African Languages, 1990)
Although traditional grammars devote attention to tense as a verbal category, the category of time is disregarded in Zulu (and the other African Languages). While tense is marked in the verb structure, time is marked, apart from the influence of tense, by (i) the semantic verb phrase categorization; (ii) the speech participants' knowledge of the world; (iii) the influence of aspectual morphemes; (iv) the influence of auxiliary verbs; (v) the text and context and (vi) the interrelation between tense forms and temporal adverbials. In this article time is discussed with emphasis on the most productive time establishing mechanism, namely the interrelation between tense forms and temporal adverbials.